2021
DOI: 10.3390/met11020181
|View full text |Cite
|
Sign up to set email alerts
|

Grain Structure, Crystallographic Texture, and Hardening Behavior of Dissimilar Friction Stir Welded AA5083-O and AA5754-H14

Abstract: This work investigated the effect of friction stir welding (FSW) tool rotation rate and welding speed on the grain structure evolution in the nugget zone through the thickness of the 10 mm thick AA5083/AA5754 weldments. Three joints were produced at different combinations of FSW parameters. The grain structure and texture were investigated using electron backscattering diffraction (EBSD). In addition, both the hardness and tensile properties were investigated. It was found that the grain size varied through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…FSW and FSP generate localized grain refinement in the whole nugget zone (NZ) behind the rotating pin tool. The FSD material is analogous to the NZ in FSW and FSP [ 17 , 36 ]. It was found that the presence of a refined, equiaxed grain structure engaged with the formation of high-angle grain boundaries is an indication of the dynamic recrystallization in FSW of AA2219-T8 [ 9 ] and FSP of AA2024/Al 2 O 3 nanocomposite [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FSW and FSP generate localized grain refinement in the whole nugget zone (NZ) behind the rotating pin tool. The FSD material is analogous to the NZ in FSW and FSP [ 17 , 36 ]. It was found that the presence of a refined, equiaxed grain structure engaged with the formation of high-angle grain boundaries is an indication of the dynamic recrystallization in FSW of AA2219-T8 [ 9 ] and FSP of AA2024/Al 2 O 3 nanocomposite [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low porosity and low residual stress are the main privileges of the as-deposited part; this will make post-processing heat treatment unnecessary in many cases. However, surface finishing will usually be required [ 15 , 16 , 17 ]. Boeing and Airbus companies are considered the first use of additive manufacturing (AM) based on FSW principles [ 10 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These microstructure features confirmed the data obtained by OM. The AFS-D has a thermomechanical zone like the stir zone in FSP [45,46]. SEM investigation by Choi et al [47] showed that the plate-like Si particles were broken into slightly finer particles by the action of tool stirring during the FSP for A356.…”
Section: Microstructure Of the Consumable Rod And A356 Ampsmentioning
confidence: 99%
“…Friction stir welding (FSW) is a solid-state welding process [43][44][45][46] that has been used at the laboratory scale for welding both low-softening-temperature materials (Al, Cu, Mg) [45][46][47][48] and high-softening-temperature materials (Ti, Ni, steel alloys) [49][50][51]. However, in terms of industrial applications, only low-softening-temperature materials find their way into a large number of applications, such as shipbuilding, railway, aerospace and automotive [44].…”
Section: Fsw Tool For High-softening-temperature Materialsmentioning
confidence: 99%